New Hybrid Scaffolds Based on 5-FU/Curcumin: Synthesis, Cytotoxic, Antiproliferative and Pro-Apoptotic Effect - Gustavo Moreno-Quintero; Emmanuel Betancur-Zapata; Angie Herrera-Ramírez; Wilson Cardona-Galeano (MDPI AG, 2023)
A series of 5-FU-Curcumin hybrids were synthesized, and their structures were elucidated by spectroscopic analysis. The synthesized hybrid compounds were evaluated in different colorectal cancer cell lines (SW480 and SW620) and in non-malignant cells (HaCaT and CHO-K1), to determine their chemopreventive potential. Hybrids 6a and 6d presented the best IC50 value against the SW480 cell line with results of 17.37 ± 1.16 µM and 2.43 ± 0.33 µM, respectively. Similarly, compounds 6d and 6e presented IC50 results of 7.51 ± 1.47 µM and 14.52 ± 1.31 µM, respectively, against the SW620 cell line. These compounds were more cytotoxic and selective than curcumin alone, the reference drug 5-fluorouracil (5-FU), and the equimolar mixture of curcumin and 5-FU. In addition, hybrids 6a and 6d (in SW480) and compounds 6d and 6e (in SW620) induced cell cycle arrest in S-phase, and, compounds 6d and 6e caused a significant increase in the sub-G0/G1 phase population in both cell lines. Hybrid 6e was also observed to induce apoptosis of SW620 cells with a respective increase in executioner caspases 3 and 7. Taken together, these results suggest that the hybrids could actively act on a colorectal cancer model, making them a privileged scaffold that could be used in future research.